A large area tactile sensor patch based on commercial force sensors - Barquero, María José; Castellanos-Ramos, Julián; Sánchez-Durán, José Antonio; Serón-Barba, Javier; Vidal-Verdú, Fernando; Navas-González, Rafael Jesús; García-Cerezo, Alfonso José (MDPI, 2011)
This paper reports the design of a tactile sensor patch to cover large areas of robots and machines that interact with human beings. Many devices have been proposed to meet such a demand. These realizations are mostly custom-built or developed in the lab. The sensor of this paper is implemented with commercial force sensors. This has the benefit of a more foreseeable response of the sensor if its behavior is understood as the aggregation of readings from all the individual force sensors in the array. A few reported large area tactile sensors are also based on commercial sensors. However, the one in this paper is the first of this kind based on the use of polymeric commercial force sensing resistors (FSR) as unit elements of the array or tactels, which results in a robust sensor. The paper discusses design issues related to some necessary modifications of the force sensor, its assembly in an array, and the signal conditioning. The patch has 16 × 9 force sensors mounted on a flexible printed circuit board with a spatial resolution of 18.5 mm. The force range of a tactel is 6 N and its sensitivity is 0.6 V/N. The array is read at a rate of 78 frames per second. Finally, two simple application examples are also carried out with the sensor mounted on the forearm of a rescue robot that communicates with the sensor through a CAN bus.
Keywords: Transductores de presión; Autómatas; Tactile sensors; Assistive robots; Human-machine interaction; Force sensing resistors